The predictors of quality of life of coronary heart disease patients: a study in Türkiye - ÇELİK, YUSUF (My University, 2023)
Aim: The aim of this study was to examine the predictors of the quality of life of patients whohave coronary heart disease in Turkey.Methods: The sample consisted of 796 participants with coronary heart disease selected from anation-ally representative 2019 Turkey Health Survey. The effects of individual-level,individuallevel healthy behaviors, household-level, and regional-level characteristics on quality oflife were analyzed by using nested regression in STATAResults: The majority of respondents were male (62.3%), relatively more aged (41.0%), married(70.5%), and primary school educated (50.6%). More than 18 percent of respondents (144 people)said that they were unable to pay for the needed medical care. The variables lessening the qualityof life for patients with coronary heart disease were found to be as female gender, increasing age,decreasing education level, living with a person with bad health status in the same house, inabilityto pay for medical care and living in statistical region-8 of Türkiye.Conclusion: The results of this study contribute to the debate concerning the expected andunexpected relationships between QoL and its predictors among respondents with patients whohave coronary heart disease. The study suggests that appropriate local and national policies shouldbe developed to improve quality of life of coronary heart disease patients.Anahtar Kelimelerpatient,coronary heart disease,quality of life,predictors,Türkiye
Keywords: Sağlık Yönetimi; Sosyal ve Beşeri Bilimler; Healthcare Management; Social Sciences and Humanities; Sosyal Bilimler (SOC); Social Sciences (SOC); Patient; Coronary Heart Disease; Quality Of Life; Predictors; Türkiye